Description and Analysis of Madrasah Diniyah in Southern Kalimantan - Husnul Yaqin; Norlaila Norlaila (Lafadz Jaya Publisher, 2024)
One of Islamic educational institutions that still exists and is acknowledged by the community and the government is Madrasah Diniyah (Islamic School) which, in the past period, was recognized as Arabic School. This institution has been strengthened by the government regulation of the Republic of Indonesia, Number 55/2007 about Religion Education and Religious Education. In line with the rapid growth of educational institutions in Indonesia in the last decade, it is important to look at the existance and the role of Madrasah Diniyah as well as its contributions in developing Indonesian Human Resource. In particular, this article is intended to have a look at its existence in the area of curriculum, teaching-learning process, and management. By using qualitative approach, 20 Madrasah Diniyahs were researched spreading in 4 regions in South Kalimantan, namely Barito Kuala, Banjar, Tanah Laut, and Hulu Sungai Tengah. The research findings indicate that the curriculum of Madrasah Diniyah in South Kalimantan varies, consisting of 1) The curriculum is in accordance with the curriculum policy of Department of Religious Affairs; 2) Adopting the curriculum of Religious Affairs Department and, at the same time, adopting essential Islamic knowledge written in Islamic-Arabic books (Malay Arab); 3) The curriculum developed by Madrasah Diniyah itself. In the context of teaching and learning process, it is conducted classically with simple media and various methods, using standard books used at Pondok Pesantren. In the context of management, Madrasah Diniyah is simply managed and still needs good administration.